MODELING OF THE PROCESS OF FUNCTION A CLEANING UNIT OF GRAIN - U.I. ERMOLJEV; M.U. KOCHKIN (Advanced Engineering Research, 2007)
A general approach of a mathematical model building of function a cleaning unit of grain with different structural schemes is given, a rational parameters and functional indexes are synthesis.